An evaluation of the hydrologic relevance of lateral flow in snow at hillslope and catchment scales. Issue 5 (24th January 2013) - Eiriksson, David; Whitson, Michael; Luce, Charles H.; Marshall, Hans Peter; Bradford, John; Benner, Shawn G.; Black, Thomas; Hetrick, Hank; McNamara, James P.; Tetzlaff, Doerthe; Carey, Sean; Soulsby, Chris
Abstract Lateral downslope flow in snow during snowmelt and rain‐on‐snow (ROS) events is a well‐known phenomenon, yet its relevance to water redistribution at hillslope and catchment scales is not well understood. We used dye tracers, geophysical methods, and hydrometric measurements to describe the snow properties that promote lateral flow, assess the relative velocities of lateral flow in snow and soil, and estimate volumes of downslope flow. Results demonstrate that rain and melt water can travel tens of metres downslope along layers within the snowpack or at the snowpack base within tens of hours. Lateral flow within the snowpack becomes less likely as the snowpack becomes saturated and stratigraphic boundaries are destroyed. Flow along the base can be prevalent in all snowpack conditions. The net result of lateral flow in snow can be the deposition of water on the soil surface in advanced downslope positions relative to its point of origin, or direct discharge to a stream. Although both melt and ROS events can redistribute water to downslope positions, ROS events produced the most significant volumes of downslope flow. Direct stream contributions through the snowpack during one ROS event produced up to 12% of streamflow during the event. This can help explain rapid delivery of water to streams during ROS events, as well as anomalously high contributions of event water during snowmelt hydrographs. In catchments with a persistent snowpack, lateral redistribution of water within the snowpack should be considered a relevant moisture redistribution mechanism. Copyright © 2012 John Wiley & Sons, Ltd.